2013
DOI: 10.1038/aja.2012.145
|View full text |Cite
|
Sign up to set email alerts
|

Glutamate, a metabolic biomarker of aggressiveness and a potential therapeutic target for prostate cancer

Abstract: G lutamate is extensively involved in metabolic and oncogenic pathways. Univariate and multivariate analyses showed that serum glutamate levels directly correlated with Gleason score (f6 vs. o8) and primary prostate cancer (PCa) aggressiveness. Compared with Caucasian Americans, serum glutamate levels were higher in African Americans with metastatic castrateresistant PCa than in the patients with primary tumors. Glutamate deprivation or blockade with pharmacological inhibitors of glutamate release or metabotro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 8 publications
0
16
0
1
Order By: Relevance
“…Glu is extensively involved in metabolic and oncogenic pathways. Koochekpour showed that serum Glu levels correlated directly with Gleason scores (<6 versus >8) and primary PCa aggressiveness. In our study, decreased Glx ratios were found in cancerous locations, but were not statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…Glu is extensively involved in metabolic and oncogenic pathways. Koochekpour showed that serum Glu levels correlated directly with Gleason scores (<6 versus >8) and primary PCa aggressiveness. In our study, decreased Glx ratios were found in cancerous locations, but were not statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…Non-CNS cancers also secrete glutamate in a manner likely mediated by Na + -independent cysteine/glutamate exchangers [125,126] and vesicular glutamate transporters (vGlut) [127]. Clinically, serum glutamate positively correlates with cancer progression and invasiveness [128], and the protumor effects of glutamate appear to be largely mediated by NMDARs. NMDARs have been identified in a wide variety of tumor types and cancer cell lines (Table 2), and, regardless of subunit configuration, NMDAR blockade reduces both cancer cell proliferation and invasiveness across many different cancers [129][130][131][132][133][134][135][136][137].…”
Section: Therapeutic Perspectivesmentioning
confidence: 99%
“…Furthermore, we have also detected extracellular Glu release in Glu-depleted conditioned media collected from different PCa cell lines (Koochekpour et al , unpublished data). In addition, our descriptive pilot study demonstrated mGluR1a (also known as GRM1a) overexpression in primary and metastatic PCa tissues 31, 32.…”
Section: Glutamate and Glutamate Receptors In Prostate Cancer Cells Amentioning
confidence: 71%
“…Furthermore, many studies have indicated that mGluRs are the predominant mediators of glutamatergic signaling in cancer. Importantly, mGluR1 was recently found to be overexpressed in human prostate tumors and further, serum Glu levels correlated with primary prostate cancer (PCa) aggressiveness 31, 32. In addition, rodent mGluR1 protein expression has been shown to cause phenotypes associated with cellular transformation in cultured melanocytes 33, 34.…”
Section: Introductionmentioning
confidence: 99%